MEDIA, GLOBALISASI DAN ANCAMAN TERORISME - sukoco, agung; Syauqillah, Muhamad; Ismail, Asep Usman (Journal of Terrorism Studies, 2021)
The advances in science and technology are also used by terrorist groups to carry out their actions, starting from propaganda, recruitment, training, communication, fundraising and even searching for information in the context of determining targets for terror attacks. In addition, along with changes in the pattern of recruiting and método acts of terror, it does not rule out the possibility of cyber terrorism attacks. This cyber terrorism attack will lead to vital facilities that are directly related to public services. Acts of terror through cyber attacks will have a wider impact and can even damage the system of a country. In order to fight cyber terrorism, what must be used is cyber counterterrorism capabilities. This can be done, among others, by cyber patrol (cyberspace), cyber deterrence, cyber prosecution and cyber surveillance.